Cancer burden in four countries of the Middle East Cancer Consortium (Cyprus; Jordan; Israel; Izmir (Turkey)) with comparison to the United States surveillance; epidemiology and end results program. (October 2016) - Anton-Culver, Hoda; Chang, Jenny; Bray, Freddie; Znaor, Ariana; Stevens, Lisa; Eser, Sultan; Silverman, Barbara; Nimri, Omar; Pavlou, Pavlos; Charalambous, Haris; Demetriou, Anna; Ward, Kevin; et al.
Highlights: Novel centralized statistical analysis was used to compare cancer registry data from four Middle East countries by creating common data dictionary and standardized analysis codes. Site-specific cancer rates differ between the four countries. Age-standardized rate of male lung cancer in Izmir/Turkey is significantly higher than other countries and is five times that in Jordan. The highest Female breast cancer rate was in Israeli Jews and lowest in Turkish women. The results can have implications for opportunities in cancer control and prevention in developing countries. Abstract: It is important that population-based cancer registries provide accurate and reliable data for public health purposes. These data are essential data for planning of cancer control and prevention. In this study, we examined cancer incidence rates (year 2005–2010) in four MECC registries (Cyprus, Jordan, Israel, Izmir (Turkey)) and compared with the rates in the US. The overall age-standardized incidence rates for males were highest in the US followed by Israeli Jews, Izmir (Turkey), Cyprus, Israeli Arabs, and lowest in Jordan. In women the rates of cancer of all sites were also highest in US women followed by Israeli Jews, Cyprus, Israeli Arabs, Izmir (Turkey), and lowest in Jordan. It is of interest that although site-specific cancer rates differ between the countries studied, prostate, lung and colorectal cancers are within the five most common cancers males in all countries studied. In females, breast colorectal and endometrium cancers are three of the five most common cancers in females in all countries studied. The results presented in this paper can have implications for opportunities in cancer control and prevention in these countries. Future studies on individual cancer sites with highest rates in these Countries are currently underway.